MIMO Detection and Equalization for Single-Carrier Systems Using the Alternating Direction Method of Multipliers - Dinis, Rui (2018)
In this letter, a multiple-input multiple-output (MIMO) detection algorithm based on the alternating direction method of the multipliers (ADMM) is proposed for single carrier transmissions in time dispersive channels. The ADMM is applied as a heuristic to solve the maximum likelihood detection problem for arbitrary signal constellations formulated in the frequency domain. This approach allows most of the decoding steps to be implemented in the frequency domain with an overall reduced complexity cost. Simulation results show that performances close to the matched filter bound can be attained in large problem sizes, even in overloaded scenarios.